Peran Kebijakan Moneter dalam Mengendalikan Inflasi: Studi Kepustakaan - Ifan Mujiadi; Arya Al-fitra Asyhari; Ahmad Ghondur (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research analyzes the role of monetary policy in controlling inflation through a literature study. Monetary policy, with instruments such as interest rates, open market operations, and minimum cash reserves, plays an important role in stabilizing prices. Literature analysis shows that the effectiveness of monetary policy in controlling inflation is highly dependent on economic conditions, political stability and public expectations. In addition, monetary policy sometimes faces limitations in dealing with global crises, which require fiscal policy support for optimal results. It is hoped that the results of this research can become a reference for more effective policies in controlling inflation in the future.